The complete guide to fasting : heal your body through intermittent, alternate-day, and extended fasting - Fung, Jason; Moore, Jimmy, 1971- (Las Vegas : Victory Belt Publishing, 2016)
"Thousands of books have been written about the latest and greatest diets that will help people lose weight and improve health. But a key element in any successful nutritional health program is a tried-and-true method that most people haven&t thought about--yet it could be revolutionary for taking health to the next level. This ancient secret is fasting. Fasting is not about starving oneself. When done right, it's an incredibly effective therapeutic approach that produces amazing results regardless of diet plan. In fact, Toronto-based nephrologist Dr. Jason Fung has used a variety of fasting protocols with more than 1,000 patients, with fantastic success. In The Complete Guide to Fasting, he has teamed up with international bestselling author and veteran health podcaster Jimmy Moore to explain what fasting is really about, why it's so important, and how to fast in a way that improves health. Together, they make fasting as a therapeutic approach both practical and easy to understand,"--Amazon.com.
Part I: What is fasting and why is it good for you? -- What is fasting? -- A brief history of fasting -- Busting the myths of fasting -- The advantages of fasting -- Fasting for weight loss -- Fasting for type 2 diabetes -- Fasting for a younger, smarter you -- Fasting for heart health -- What you need to know about hunger -- Who should not fast? -- Part II: How to fast -- Kinds of fasts and best practices -- Intermittent fasting -- Longer periods of fasting -- Extended fasting -- Fasting tips and FAQs -- Part III: Resources -- Fasting fluids -- 24-hour fasting protocol -- 36-hour fasting protocol -- 48-hour fasting protocol -- 7- to 14-day fasting protocol -- Recipes.
Includes bibliographical references and index.
Keywords: fasta